Salivary S100A8/A9 in Sjögren's syndrome accompanied by lymphoma. (6th August 2018) - Jazzar, Ahoud A.; Shirlaw, Penelope J.; Carpenter, Guy H.; Challacombe, Stephen J.; Proctor, Gordon B.
Abstract : Background: Sjögren's syndrome (SS) is an autoimmune inflammatory disease that affects the exocrine glands. The absence of early diagnostic markers contributes to delays in its diagnosis. Identification of changes in the protein profile of saliva is considered one of the promising strategies for the discovery of new biomarkers for SS. Objective: To identify salivary protein biomarkers with potential for use in discriminating between different lymphoma risk subgroups of SS. Method: Parotid and whole mouth saliva samples were collected from patients with SS, including those in subgroups at higher risk of developing or with confirmed lymphoma, non‐SS sicca disease controls and healthy subjects. An initial proteomics analysis by mass spectrometry (LCMSMS) identified S100A8/A9 as a biomarker and was followed by validation with an enzyme‐linked immunosorbent assay (ELISA). Results: Significant differences were found in levels of S100A8/A9 in parotid saliva but not whole mouth saliva between patients with SS compared with healthy and disease control subjects ( P = 0.001 and 0.031, respectively). Subgroups of patients with SS based on lymphoma risk showed significant differences in salivary levels of S100A8/A9. Conclusion: The results suggest that salivary levels of S100A8/A9 can aid in differentiating between SS, disease control and healthy control subjects, especially the subgroups of SS with lymphoma or at higher risk of lymphoma.